Mechanism of Diamond-Like Carbon (DLC) Delamination under Rolling Contact Condition - Tsutomu Sato (Japanese Society of Tribologists, 2008)
Diamond-like carbon (DLC) is being advanced as an excellent surface modification technology for a growing number of applications because of its low friction coefficient and excellent wear resistance. Due to the excellent characteristics of certain mechanical elements, such as a bearing, high levels of functionality are expected. Unfortunately, it is difficult to take full advantage of such high functionality because of insufficient endurance under high-pressure operating conditions. In order to make use of DLC as a bearing surface coating, the mechanism of DLC delamination under high-pressure conditions needs to be clarified. This paper discusses the mechanism of delamination of the intermediate layer of a DLC coating on a bearing in a test rig and by numerical simulation using FEM analysis. Test results revealed that the smaller the Young's modulus value of the intermediate layer (a factor affecting durability) of the DLC coating, the greater the resistance to delamination.